NEUROPLASTICITY OF THE BRAIN AND MODERN PEDAGOGICAL APPROACHES TO FOREIGN LANGUAGE LEARNING: OVERCOMING AGE BARRIERS, STIMULATING COGNITIVE FUNCTIONS, AND IMPROVING PRONUNCIATION - Bondarenko , Yaroslav; Petrova , Olha; Kauk , Oksana; Zelenska , Kateryna (Collection of scientific papers «ΛΌГOΣ», 2025)
Relevance. Studying foreign languages is essential to modern life and part of cognitive development throughout ontogenesis, presenting unique challenges and barriers for people of various age groups. Neuroplasticity plays a significant role in learning and development processes. Neuroplasticity, also known as brain plasticity, is the process that includes adaptive structural and functional changes in the brain. A suitable definition is "the ability of the nervous system to alter its activity in response to internal or external stimuli by reorganizing its structure, functions, or connections" [17]. Research on neuroplasticity demonstrates that the brain can adapt and change neural connections throughout life; however, this ability decreases with age. Thus, the challenge arises of achieving the most influential foreign language learning at different ages by applying modern pedagogical approaches that consider the brain’s neuroplasticity, its physiology, and the characteristics of the individual language learner. This study is relevant for improving foreign language education and developing effective strategies to overcome psychological barriers.